National Crime Victimization Survey: Stalking Victimization Supplement, 2006 ([Verlag nicht ermittelbar], 2009)
The Supplemental Victimization Survey (SVS) was designed to measure the prevalence, characteristics, and consequences of nonfatal stalking so that policymakers, academic researchers, practitioners at the federal, state and local levels, and advocates could make informed decisions concerning policies and programs. The SVS asks questions related to victims' experiences of unwanted contact or harassing behavior on two or more occasions during the previous 12 months. The survey provides information about the following dimensions of stalking behavior: relationship of the perpetrator to victim; onset, duration, and desistance; other crimes and injuries committed against the victim in conjunction with stalking; victim response; criminal justice response; and cost to victim. These responses are linked to the National Crime Victimization Survey (NCVS) survey instrument responses for a more complete understanding of the stalking victim's circumstances. The 2006 SVS was a one-time supplement to the annual NCVS to obtain specific information about stalking victimization on a national level. This supplement was sponsored by the Office of Violence Against Women (OVW) in the United States Department of Justice. Since the SVS is a supplement to the NCVS, it is conducted under the authority of Title 42, United States Code, Section 3732. Only Census employees sworn to preserve confidentiality may see the completed questionnaires.